IMPLEMENTATION OF CHARACTER EDUCATION OF ENVIRONMENTAL CARE ATTITUDE IN STUDENTS AT STATE ELEMENTARY SCHOOL 15 BANDAR BARU, PIDIE JAYA DISTRICT - Rengganis, Putri Ayu; Ahadin, Ahadin; Sulaiman, Sulaiman (Elementary Education Research, 2024)
The character of caring for the environment must be instilled by getting children used to washing their hands during recess and washing their hands before eating and after eating. All students are also taught to keep the bathroom and hand washing area clean. School cleanliness is the responsibility of all school members without exception. The formulation of the research problem is how to implement the instilling of environmentally caring attitudes in students in grades III and V at SD Negeri 15 Bandar Baru? The aim of the research is to describe the implementation of instilling environmentally caring attitudes in students in grades III and V at SD Negeri 15 Bandar Baru, Pidie Jaya Regency. The approach used is a qualitative approach with a descriptive type. The research location is SD Negeri 15 Bandar Baru, Pidie Jaya Regency. The research subjects taken were the school principal, class IIIA, IIIB and class V homeroom teachers. Data collection techniques were through observation and interviews, while data analysis used data reduction, data presentation and drawing conclusions. The results obtained in this research are that the implementation of environmental care character education is very good, the teachers understand what is being directed and the purpose of this, starting from focusing on the cleanliness of the school environment and also adding to the beauty of the school, but there are still things that can be improved and developed. such as education about the differences in waste, it can be seen from the results of observations for the program for separating or differentiating waste between organic and inorganic waste. Not all students understand this and it is also possible that education is only given by the district office and without a clear follow-up program. Implementation for high classes (Class V) has begun to be implemented well by implementing routine school cleaning and problems such as rubbish left behind or putting paper waste under desk drawers may still be a problem.